2011
DOI: 10.1126/scitranslmed.3003084
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Dengue Disease Severity Determined by the Interplay Between Viral Genetics and Serotype-Specific Immunity

Abstract: The rapid spread of dengue is a worldwide public health problem. In two clinical studies of dengue in Managua, Nicaragua, we observed an abrupt increase in disease severity across several epidemic seasons of dengue virus serotype 2 (DENV-2) transmission. Waning DENV-1 immunity appeared to increase the risk of severe disease in subsequent DENV-2 infections after a period of cross-protection. The increase in severity coincided with replacement of the Asian/American DENV-2 NI-1 clade with a new virus clade, NI-2B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
282
4
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 267 publications
(315 citation statements)
references
References 93 publications
17
282
4
3
Order By: Relevance
“…However, the highest frequency of severe forms in DENV-2 infections was observed in Southeast Asia and in Latin America. 13,15,21,22,26 The DENV-2 was recently found to be significantly associated with DSS in several countries. 27 However, all serotypes could lead to severe forms and death 1 ; among the deaths observed during the study period, one notes that half were attributed to cardiovascular-associated disease, diabetes, sickle cell disease, or nosocomial infections contracted in intensive care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the highest frequency of severe forms in DENV-2 infections was observed in Southeast Asia and in Latin America. 13,15,21,22,26 The DENV-2 was recently found to be significantly associated with DSS in several countries. 27 However, all serotypes could lead to severe forms and death 1 ; among the deaths observed during the study period, one notes that half were attributed to cardiovascular-associated disease, diabetes, sickle cell disease, or nosocomial infections contracted in intensive care.…”
Section: Discussionmentioning
confidence: 99%
“…A recent publication showed that secondary DENV-2 infections could result from more virulent clades than others, depending on the serotype of the primary infecting serotype, DENV-1 or DENV-3. 21 Under these conditions, the development dynamics of epidemics, the function of the implicated genotypes, and the intervals between the successive epidemics, 22 the immune and genetic status of the population, 23 and other environmental factors such as the population density, 24 the climate and density of mosquitoes of the Aedes genus, 25 could create specific situations in each endemic region and thus create many confounding factors. This could explain the differences in results shown in various publications on the theme of clinical presentation by serotype.…”
Section: Discussionmentioning
confidence: 99%
“…36,51,58 Notably, although other lineage/genotype replacement events associated with increased disease severity involved a period of lineage/genotype cocirculation, the southeast Asian/American lineage II viruses from our study were introduced into Loreto in the absence of any DENV-2 competitors. 59,60 It is clear that both host and viral factors can play a role in determining dengue disease severity. Our results indicate that the large number of severe dengue cases observed during the 2010 and 2011 Loreto outbreak was not associated with increased viral replication in human mo-DCs or dissemination in mosquitoes.…”
Section: Denv-2 Lineage II Peru Outbreakmentioning
confidence: 99%
“…27,61 Even more specifically, it has been shown that disease severity in the context of a given immunological background can be affected by the genotype/clade of the DENV-2 infecting virus. 59,62 In Iquitos, a single DENV serotype typically dominates, and historically, the introduction of new DENV serotypes has resulted in epidemics of DF. These epidemics in Iquitos have been well-documented and were marked by the introduction of American DENV-2 in 1995, DENV-3 in 2001, and DENV-4 in 2008.…”
Section: Denv-2 Lineage II Peru Outbreakmentioning
confidence: 99%
“…The sequence of infecting DENV serotypes can modulate disease severity (20). Defining the sequence of infecting DENV serotypes is difficult, except in the context of cohort studies, where individuals are followed longitudinally over many years and have wellcharacterized sequential DENV infections.…”
Section: A Protective Role For Original Antigenic Sinmentioning
confidence: 99%